Engineering rhizobacteria as synthetic biology chassis - Grant, K (2019)
In the next half-century the world will face an enormous food deficit due to a raising birth rate and longer life-spans of the global population. By 2050 there will be 9.5 billion people in the world who will require a 69% increase from current total food calories to prevent global starvation. Widespread hunger and starvation are linked directly to the productivity of crop growth and productivity in agriculture, especially in the third world. By 2030, Areas such as sub-Saharan Africa and Australia are predicted to have a 37% and 48% decrease in crop productivity respectively due to global warming. The first ‘Green Revolution’ increased the world’s crop output by an order of magnitude using synthetic nitrogen fertilisers derived from the Haber-Bosch process. A process which last year yielded 180 million tonnes of ammonia, 82% of which was used for the manufacture of nitrogenous fertilisers. Global usage of synthetic nitrogenous fertilisers is increasingly unsustainable and a new approach to increasing crop productivity is required to face the ever-increasing food demands over the next 30 years. In this project we have contributed to the engineering of biofertilisers and plant growth promoting rhizobacteria that could alleviate the use of inorganic fertilisers and chemicals and serve as an economically viable alternative in developing countries. Synthetic biology tools and techniques are employed to engineer two model rhizobacteria. Azorhizobium caulinodans ORS571 and Azospirillum brasilense FP2, two nitrogen-fixing and known plant-associative rhizobacteria, are used as chassis. A suite of synthetic biology tools are characterised for the two rhizobacteria species as exemplars of the toolkit being used for the engineering of other significant rhizobacteria. Advanced logic-gate based genetic circuitry is developed to yield functional genetic circuits that can be engineered with characterised plant growth promotion (PGP) effectors to yield agriculturally-relevant phenotypes. A suite of these PGP mechanisms including auxin biosynthesis, phosphate solubilisation and antifungal compound (DAPG) biosynthesis, are built and characterised in both rhizobacterial strains The novel implementation of a CRISPR interference technology (CRISPRi) is demonstrated in both chassis. Genomic targeting of dCas9 is implemented to control the ammonia assimilation pathway of A. brasilense FP2 with the effect of significant ammonia release into growth media. This work builds the foundations for the future engineering of both logical genetic circuitry and the CRISPRi system with an input from a unique associative crop plant signal. This will allow a rhizosphere-specific phenotypic switch of the rhizobacteria from a fast-growing competitive state to a plant beneficial ammonia secreting state.